Environmentally Friendly Materials Use Strategy on Heirloom Houses of Mandailing Community in Mountainous Area (Case Studies : Heirloom Houses in Singengu and Habincaran) - Nuraini, Cut; Walid, Hibnul; Fitri Handayani Nasution, Meyga; Kesuma Hadi, Indra; ., Suprayitno (International Journal of Engineering and Technology, 2018)
The ancestor of Mandailing etnic whom lived on mountainous area, since long times ago have been understood about the environmentally friendly materials use strategy for the dwelling. The use of environmentally friendly materials has been found on some bagas pusako (heirloom houses) in two main villages that called huta induk, such as Singengu and Habincaran. This research aims to reveal the strategy of heirloom houses that has been used environmentally friendly materials. The research is uses descriptive-qualitative methode with deductive analysis and focused on sustainable design strategy especially about the material and resources. The result shows that environmentally friendly materialsuse strategy of heirloom houses of Mandailing etnic in Singengu and Habincaran has been done with three part of building, such as at the bottom of building, in the middle of building, and the top of building. The strategies are 1) natural stone for foundation; 2) local wood (ingui) for pole, beam, stair, and windows; 3) gogat (local bamboo) for wall and floor; and 4) iju/rumbia or fibers for roof cover. Residential process of heirloom houses as over the time and the changing of the residents or the heirs have been caused of changes in material use.Â Â Â